Study on the effects of land use transformation on habitat quality and its driving mechanisms: a case study of the Qin-Mang River Basin - Zhao, Jiwei; Wang, Luyao; Jia, Dong; Wang, Yaowen (Frontiers in Environmental Science, 2025)
Habitat quality (HQ) is a critical factor for regional ecosystem health and sustainable development, as well as an important basis for formulating ecological protection and land-use planning. The Qin-Mang River Basin, as an integral part of the biodiversity conservation area in the Yellow River Basin, plays a significant role in maintaining the balance and stability of the regional ecosystem. This study is based on land use/land cover changes (LUCC) data from 1992, 2002, 2012, and 2022. It employs a land use transfer matrix to analyze the dynamic trends and patterns of LUCC. HQ changes are evaluated using the InVEST model, and the GeoDetector model is used to identify the key driving factors and their interactions. Additionally, spatial autocorrelation analysis is applied to explore the spatial clustering characteristics of HQ. The results indicate that between 1992 and 2022, the cumulative area of land transfer in the study area exceeded 600 km2, primarily characterized by the conversion of cultivated land to built-up areas. The HQ index decreased from 0.3409 in 1992 to 0.2896 in 2022, with a significant increase in spatial heterogeneity. Altitude, vegetation coverage, temperature, precipitation, and slope are the main driving factors influencing HQ, with natural factors dominating, but human activities gradually playing an increasingly significant role. Furthermore, HQ exhibits significant spatial clustering characteristics, with hotspot and coldspot areas providing scientific evidence for ecological protection and restoration measures. To improve HQ, it is recommended to strictly enforce ecological protection red lines, control the expansion of built-up areas, improve ecological compensation mechanisms, and promote ecological restoration measures such as returning farmland to forest and grassland.